Examination of the effectiveness of Renzulli’s Enrichment Triad Program on Creativity of sharp-witted primary school level students - mozhgan shoushtari; mokhtar malekpour; احمد عابدی; امیر قمرانی (Ravānshināsī-i Afrād-i Istis̠nāyī, 2016)
Abstract The current research aimed to investigate the effectiveness of Renzulli’s Enrichment Triad Program on Creativity of sharp-witted primary school level students. . research method was Experimental with pretest - posttest and control group. The statistical universe of the current research consisted of all sharp-witted students of the city of Karaj in the educational year of 2015-2016. For this purpose, the number of 76 sharp-witted students was selected through multi stage cluster random sampling method and was randomly placed in two experimental and control groups (38 people in the experimental group and another 38 in the control group) and their mothers, too responded to the questions of Abedi’s Creativity. The experimental group , During the twelve two-hour sessions The Renzulli’s Enrichment Triad Program was administered on the experimental group but The control group not received training in this issue . The research Data were collected by Abedi’s Creativity Test and with analysis of covariance (MANCOVA) were analyzed .The findings showed that Renzulli’s Enrichment Triad Program has been effective in increasing female creativity. In general it can be concluded that Renzulli’s Enrichment Triad Program Can affect on children's creativity.